Chitosan nanoparticles as carriers for the delivery of ΦKAZ14 bacteriophage for oral biological control of colibacillosis in chickens - Kaikabo, Adamu Ahmad; Mohammed, Abdulkarim Sabo; Abas, Farida (MDPI, 2016)
The use of chitosan as a delivery carrier has attracted much attention in recent years. In this study, chitosan nanoparticles (CS-NP) and chitosan-ΦKAZ14 bacteriophage-loaded nanoparticles (C-ΦKAZ14 NP) were prepared by a simple coercavation method and characterized. The objective was to achieve an effective protection of bacteriophage from gastric acids and enzymes in the chicken gastrointestinal tract. The average particle sizes for CS-NP and C-ΦKAZ14 NP were 188 ± 7.4 and 176 ± 3.2 nm, respectively. The zeta potentials for CS-NP and C-ΦKAZ14 NP were 50 and 60 mV, respectively. Differential scanning calorimetry (DSC) of C-ΦKAZ14 NP gave an onset temperature of −17.17 °C with a peak at 17.32 °C and final end set of 17.41 °C, while blank chitosan NP had an onset of −20.00 °C with a peak at −19.78 °C and final end set at −20.47. FT-IR spectroscopy data of both CS-NP and C-ΦKAZ14 NP were the same. Chitosan nanoparticles showed considerable protection of ΦKAZ14 bacteriophage against degradation by enzymes as evidenced in gel electrophoresis, whereby ΦKAZ14 bacteriophage encapsulated in chitosan nanoparticles were protected whereas the naked ΦKAZ14 bacteriophage were degraded. C-ΦKAZ14 NP was non-toxic as shown by a chorioallantoic membrane (CAM) toxicity assay. It was concluded that chitosan nanoparticles could be a potent carrier of ΦKAZ14 bacteriophage for oral therapy against colibacillosis in poultry.